Selenoproteins and their emerging roles in signaling pathways - Stanishevska, N. V. (Regulatory Mechanisms in Biosystems, 2020)
The functional activity of selenoproteins has a wide range of effects on complex pathogenetic processes, including teratogenesis, immuno-inflammatory, neurodegenerative. Being active participants and promoters of many signaling pathways, selenoproteins support the lively interest of a wide scientific community. This review is devoted to the analysis of recent data describing the participation of selenoproteins in various molecular interactions mediating important signaling pathways. Data processing was carried out by the method of complex analysis. For convenience, all selenoproteins were divided into groups depending on their location and function. Among the group of selenoproteins of the ER membrane, selenoprotein N affects the absorption of Ca2+ by the endoplasmic reticulum mediated by oxidoreductin (ERO1), a key player in the CHOP/ERO1 branch, a pathogenic mechanism that causes myopathy. Another selenoprotein of the ER membrane selenoprotein K binding to the DHHC6 protein affects the IP3R receptor that regulates Ca2+ flux. Selenoprotein K is able to affect another protein of the endoplasmic reticulum CHERP, also appearing in Ca2+ transport. Selenoprotein S, associated with the lumen of ER, is able to influence the VCP protein, which ensures the incorporation of selenoprotein K into the ER membrane. Selenoprotein M, as an ER lumen protein, affects the phosphorylation of STAT3 by leptin, which confirms that Sel M is a positive regulator of leptin signaling. Selenoprotein S also related to luminal selenoproteins ER is a modulator of the IRE1α-sXBP1 signaling pathway. Nuclear selenoprotein H will directly affect the suppressor of malignant tumours, p53 protein, the activation of which increases with Sel H deficiency. The same selenoprotein is involved in redox regulation. Among the cytoplasmic selenoproteins, abundant investigations are devoted to SelP, which affects the PI3K/Akt/Erk signaling pathway during ischemia/reperfusion, is transported into the myoblasts through the plasmalemma after binding to the apoER2 receptor, and into the neurons to the megaline receptor and in general, selenoprotein P plays the role of a pool that stores the necessary trace element and releases it, if necessary, for vital selenoproteins. The thioredoxin reductase family plays a key role in the invasion and metastasis of salivary adenoid cystic carcinoma through the influence on the TGF-β-Akt/GSK-3β pathway during epithelial-mesenchymal transition. The deletion of thioredoxin reductase 1 affects the levels of messengers of the Wnt/β-catenin signaling pathway. No less studied is the glutathione peroxidase group, of which GPX3 is able to inhibit signaling in the Wnt/β-catenin pathway and thereby inhibit thyroid metastasis, as well as suppress protein levels in the PI3K/Akt/c-fos pathway. A key observation is that in cases of carcinogenesis, a decrease in GPX3 and its hypermethylation are almost always found. Among deiodinases, deiodinase 3 acts as a promoter of the oncogenes BRAF, MEK or p38, while stimulating a decrease in the expression of cyclin D1. The dependence of the level of deiodinase 3 on the Hedgehog (SHH) signaling pathway is also noted. Methionine sulfoxide reductase A can compete for the uptake of ubiquitin, reduce p38, JNK and ERK promoters of the MAPK signaling pathway; methionine sulfoxide reductase B1 suppresses MAPK signaling messengers, and also increases PARP and caspase 3.